New unidentate jumping spider genera (Araneae: Salticidae) from Australia - Richardson, Barry J. (Zootaxa, 2013)
The Australian fauna includes large numbers of undescribed, tiny, litter-living, jumping spiders. In this paper four monotypic new genera (Ananeon howardensis n. g. n. sp., Barraina anfracta n. g. n.sp., Frewena maculata n.g. n.s., and Pungalina weiri n.g, n.sp.) are described. Two species (Neon taylori n.sp. and Neon australis n. sp.) representing the two distinctive morphological patterns found in Australian species of this genus are also described. The former, similar in the morphology of the palp and genitalia to that found in many species from eastern Australia, is most similar in morphology to N. sumatranus Logunov 1998 from Indonesia and N. kovblyuki Logunov 2004 from the Crimea. The latter, and other similar species from South Australia and Western Australia, has palp morphology and fringing on L1 very similar to that seen in N. nojimai Ikeda 1995 from Japan.